Meiotic studies in Lygaeus alboornatus Blanchard 1852 (Heteroptera, Lygaeidae: Lygaeinae) - Bressa, María José (2002)
Fil: Bressa, María José. Facultad de Ciencias Naturales y Museo, Universidad Nacional de La Plata